Reduction of vibration of spur gears with phasing - Mohammed Irshad (2014)
In this report, the transmission error of a single stage spur gear was being analysed. The transmission error was reduced by reducing the variation mesh stiffness. This was done by using spur gears with phasing. The phasing gears used had a half pitch phasing. This report will show how the change in normal gears to phasing gears will affect the mesh stiffness. The mesh stiffness studied in this case is between a single tooth contact and a double tooth contact. The change in the mesh stiffness was then related to the transmission error in the system.